Computer organization and design : the hardware/software interface - Patterson, David A.; Hennessy, John L. (Elsevier, 2017)
This book presents the fundamentals of hardware technologies, assembly language, computer arithmetic, pipelining, memory hierarchies and I/O. This edition is updated for mobile computing and the cloud!